2017
DOI: 10.4172/2161-0665-c1-044
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal illness severity scores predict neurodevelopmental impairments at 10 years of age in children born extremely preterm

Abstract: Introduction-A neonatal illness severity score, The Score for Neonatal Acute Physiology-II (SNAP-II), predicts neurodevelopmental impairments at two years of age among children born extremely preterm. We sought to evaluate to what extent SNAP-II is predictive of cognitive and other neurodevelopmental impairments at 10 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While the SNAP score correlates well with mortality, nursing workload and length of stay, the complexity due to the large number of data elements led the investigator group to develop more user friendly versions, such as SNAP-II and SNAP-perinatal extension. 7 These observations by Logan et al 1 are informative and help build on the ELGAN study investigators' previous work looking at the association between versions of the SNAP score and mortality, 8 and brain injury in the NICU/neurodevelopment at 2 years of age. 9 While all three SNAP studies in the ELGAN cohort perform a multivariate analysis adjusting for multiple confounders, the further one gets from the event (that is, the first 12 to 24 h of birth), the more challenging it is to make the link along the causal pathway between the predictor (SNAP-II) and outcomes, which the authors acknowledge as a limitation.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…While the SNAP score correlates well with mortality, nursing workload and length of stay, the complexity due to the large number of data elements led the investigator group to develop more user friendly versions, such as SNAP-II and SNAP-perinatal extension. 7 These observations by Logan et al 1 are informative and help build on the ELGAN study investigators' previous work looking at the association between versions of the SNAP score and mortality, 8 and brain injury in the NICU/neurodevelopment at 2 years of age. 9 While all three SNAP studies in the ELGAN cohort perform a multivariate analysis adjusting for multiple confounders, the further one gets from the event (that is, the first 12 to 24 h of birth), the more challenging it is to make the link along the causal pathway between the predictor (SNAP-II) and outcomes, which the authors acknowledge as a limitation.…”
mentioning
confidence: 88%
“…Not surprisingly, the authors found that a high SNAP-II score in the first 12 h of life is associated with an increased risk of neurodevelopmental and social issues at 10 years of age. 1 The authors offer one of the four possible explanations for their findings. The first two describe that physiologic derangements early in life are on the causal pathway to brain injury, as well as other preterm morbidities (for example, sepsis, chronic lung disease (CLD), and so on), and are thus predictors of neurodevelopment.…”
mentioning
confidence: 99%
See 3 more Smart Citations